A comparative study of radiofrequency and microwave heating on functional and bioactive constituents of rice bran: Stabilization of rice bran using different methods - Sood, Monika; Nazir, Ambreena; Bandral, Julie; Salgotra, RK (ORYZA-An International Journal of Rice, 2025)
Rice bran can serve as both a food ingredient and a source of oil to meet the increasing demands. However, the lipase enzyme present in bran comes into contact with fat during milling process and causes hydrolysis of fats to free fatty acids (FFAs) and glycerol leading to the development of hydrolytic rancidity which is responsible for off-flavour development during storage. Therefore, the present investigation was carried out with the objective to study the effect of stabilization methods on functional and bioactive constituents of rice bran. The rice bran samples were adjusted at three different moisture levels viz., 18, 21 and 24 % and treated at three different exposure times viz., 160, 200 and 240 seconds using radiofrequency and microwave heating, respectively. Results revealed that highest mean water absorption capacity of 199.20 g per100g, fat absorption capacity of 91.80 g per100g and emulsifying capacity of 37.72 g per 100g were recorded in treatment T4 while as highest foaming capacity of 74.96 g per 100g was recorded in treatment T1. During storage the overall mean water absorption capacity and emulsifying capacity decreased while as fat absorption capacity and foaming capacity increased significantly. The antioxidant activity and total phenols increased with both microwave and radiofrequency heating but decreased during storage. The highest overall mean antioxidant activity of 87.85 per cent radical scavenging activity and total phenols of 5.68 mg GAE per g were observed in treatment T4 while as T1 recorded lowest values for antioxidant activity (83.62 % radical scavenging activity) and total phenols (3.62 mg GAE/g).The overall mean free fatty acid and peroxide value decreased with both microwave and radiofrequency heating from 49.90 to 3.96 per cent as oleic acid and 63.39 to 5.84 meq per kg, respectively. During storage the overall mean free fatty acid and peroxide value showed an increasing trend. Based on overall nutritional characteristics and stability, radiofrequency heating was found more effective than microwave stabilization.